The Historical Transformation of Forest Conservation in Indonesia: An Islamic Ecotheology Perspective (1910–2024) - Imran (Wasatha: Jurnal Studi Islam dan Humaniora, 2026)
This study examines the transformation of forest conservation policies and practices in Indonesia from 1910 to 2024 through the lens of Islamic ecotheology. Utilizing historical methodology—comprising heuristics, criticism, interpretation, and historiography—this research analyzes the paradigmatic shift from the colonial conservation model, characterized by an exploitative-administrative nature, toward the integration of spiritual values into modern environmental policy. The findings indicate that while formal conservation structures were established during the Dutch East Indies era, the internalization of Islamic ecotheological values—specifically the concepts of tawhid (monotheism), khalifah (stewardship), and amanah (trust)—has begun to strengthen formally within public policy over the last decade as a response to the global ecological crisis.